Histology and RNA Sequencing Provide Insights Into Fusarium Head Blight Resistance in AAC Tenacious - Nilsen, Kirby T.; Walkowiak, Sean; Kumar, Santosh; Molina, Oscar I.; Randhawa, Harpinder S.; Dhariwal, Raman; Byrns, Brook; Pozniak, Curtis J.; Henriquez, Maria A. (Frontiers in Plant Science, 2021)
Fusarium head blight (FHB) is a serious fungal disease affecting wheat and other cereals worldwide. This fungus causes severe yield and quality losses from a reduction in grain quality and contamination of grain with mycotoxins. Intensive breeding efforts led to the release of AAC Tenacious, which was the first spring wheat cultivar registered in Canada with a resistant (R) rating to FHB. To elucidate the physiological mechanisms of resistance, we performed histological and transcriptomic analyses of AAC Tenacious and a susceptible control Roblin after inoculation with Fusarium graminearum (Fg). The spikelet and rachis of infected wheat spikes were hand sectioned and monitored by confocal and fluorescent microscopy. Visible hyphae were observed within the inoculated spikelets for AAC Tenacious; however, the infection was largely restricted to the point of inoculation (POI), whereas the adjacent florets in Roblin were heavily infected. Significant cell wall thickening within the rachis node below the POI was evident in AAC Tenacious compared to Roblin in response to Fg inoculation. Rachis node and rachilla tissues from the POI and the rachis node below the POI were collected at 5 days post inoculation for RNAseq. Significant changes in gene expression were detected in both cultivars in response to infection. The rachis node below the POI in AAC Tenacious had fewer differentially expressed genes when compared to the uninoculated control, likely due to its increased disease resistance. Analysis of differentially expressed genes in Roblin and AAC Tenacious revealed the activation of genes and pathways in response to infection, including those putatively involved in cell wall modification and defense response.